Security System in the Residence Using Microcontroller and PC-based Laser. - Fridy Mandita (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
Security in residential neighborhoods is one of the factors that is desired by its inhabitans. Variety of ways conducted by the residents to make a residence occupied by having a good level of security. One of them is by installing the security tools at his residence.The main objective of this research is to design and create a safety tool on the housing using a microcontroller and PC-based transmitter with a laser beam and the light sensor. Protection systems was created using components include: AT89C51 microcontroller,ADC 0804, laser, resistors, IC7805, and IC7406. The protection system was built using Delphi programming language and Assembler. A protection system works by turning on and steer it on a light sensor. The speed of the object can be when an object blocks the laser beam which is forwarded to thelight sensor. The speed of the object can be known at any object obstruct the laser beam which is forwarded to the light sensor. Information about this will be delivered by microcontroller to the PC as a sign of danger through a series of channels i.e RS 232.